Exploring the Mechanism of Total Flavonoids of Drynariae Rhizoma to Improve Large Bone Defects by Network Pharmacology and Experimental Assessment - Sun, Weipeng; Li, Minying; Xie, Lei; Mai, Zhexing; Zhang, Yan; Luo, Lieliang; Yan, Zijian; Li, Zige; Dong, Hang; Huang, Feng; Shen, Zhen; Jiang, Ziwei (Frontiers in Pharmacology, 2021)
Drynariae Rhizoma (DR) has been demonstrated to be effective in promoting fracture healing in clinical use. In the study, we tried to predicate potential signaling pathways and active ingredients of DR via network pharmacology, uncover its regulation mechanism to improve large bone defects by in vivo and in vitro experiment. We total discovered 18 potential active ingredients such as flavonoids and 81 corresponding targets, in which mitogen-activated protein kinase (MAPK) signaling pathway has the highest correlation with bone defects in pathway and functional enrichment analysis. Therefore, we hypothesized that flavonoids in DR improve large bone defects by activating MAPK signaling pathway. Animal experiments were carried out and all rats randomly divided into TFDR low, medium, and high dosage group, model group and control group. Twelve weeks after treatment, according to X-ray and Micro-CT, TFDR medium dosage group significantly promote new bone mineralization compared with other groups. The results of HE and Masson staining and in vitro ALP level of BMSC also demonstrated the formation of bone matrix and mineralization in the TFDR groups. Also, angiographic imaging suggested that flavonoids in DR promoting angiogenesis in the defect area. Consistently, TFDR significantly enhanced the expression of BMP-2, RUNX-2, VEGF, HIF-1 in large bone defect rats based on ELISA and Real-Time PCR. Overall, we not only discover the active ingredients of DR in this study, but also explained how flavonoids in DR regulating MAPK signaling pathway to improve large bone defects.